El desarrollo psicomotriz en los niños del primer grado de la unidad educativa Cusubamba, cantón Salcedo, provincia de Cotopaxi - Baño Chimbo, Ana María (2023)
The purpose of this research work is to demonstrate the shortcomings in the psychomotor development of children, considering that the lack of psychomotor stimulation can cause permanent and irreversible consequences in the development of motor and intellectual skills of children. The objective of the research is to diagnose the psychomotor development of first grade children Educational Unit "Cusubamba", of the through the application of information collection instruments to propose alternative solutions to the integral development of infants. The methodology of this research was framed in the quantitative and qualitative approach, carried out towards a bibliographic andfield research to achieve a descriptive character in the investigation. The techniques usedin the research are the interview applied to the teacher of the first grade and rector, on the other hand, the survey was applied to parents and an observation sheet to children, with the purpose of obtaining real information about the current situation of the psychomotor development of children, which will allow the identification of strengths and weaknesses.Being a theoretically supported study, it becomes a starting point for new research that isinterested in psychomotor development. The research provides practical guidance to the teacher to carrying out activities during the development of the child, helping their explore their ability. Teachers must implement new didactic strategies that help strengthen the psychomotor development of children based on activities related to play work.